Product labeling, quality and international trade - Marion Jansen; André Lince de Faria (World Trade Organization (WTO), 2002)
This paper analyzes the reasons why countries may pursue different labeling policies in autarky and how this affects countries' welfare in the context of international trade. In an asymmetric information environment where producers know the quality of the goods they are selling and consumers are not able to distinguish between them, the quality governments choose to protect by a label depends on consumer preferences for and production costs of different qualities. Countries with different distributions of tastes and/or different production functions will thus decide to label differently. When they trade, welfare effects will be different on the country as a whole and on different types of consumers within each country depending on whether countries choose to mutually recognize each others labeling policy or to harmonize their policies. In particular it will be the case that a country with weak preferences for high quality will oppose the introduction of an international, harmonized label as it is better off under a regime of mutual recognition. When countries only differ in their costs of producing quality instead, none of the trading partners will lose from a move towards trade under an international, harmonized label.
Keywords: D82; F13; 330; Product labels; international trade; mutual recognition